Cyrtodesmus baerti, n. sp., a cryptic millipede from the Galápagos Islands, Ecuador (Diplopoda, Polydesmida, Cyrtodesmidae) - Shear, William A.; Peck, Stewart B. (Zootaxa, 2018)
Cyrtodesmus baerti, n. sp., previously reported from the Galápagos Islands, Ecuador, as Cyrtodesmus sp., is described, together with notes on the systematics, natural history and morphology of cyrotdesmid millipedes.